One-shot dual gene editing for drug-resistant pancreatic cancer therapy - Won, Eun Jeong; Park, Hyeji; Chang, Seung Hee; Kim, Jin Hyun; Kwon, Hojeong; Cho, Young Seok; Yoon, Tae Jong (Biomaterials, 2021)
It is challenging to diagnose patients with pancreatic ductal adenocarcinoma (PDAC) early on, and their treatment is often complex. Gemcitabine (GEM) is the first-line treatment for PDAC, but its efficacy is limited in most patients due to the GEM resistance from KRAS and P53 gene mutations. We describe the correction of a double gene mutation and therapeutic effect for the GEM resistant PDAC. Bio-available nanoliposomes (NL) possessing Cas9-ribonucleoproteins and adenine-base editors were developed to conduct KRAS and P53 mutation gene editing directly. NLs were conjugated with EGFR antibodies to tumor-specific delivery, and the anti-cancer effect was verified in vitro and in vivo Model. Our GEM-combinatorial therapeutic strategies using double gene editing systems with one-shot may be a potent therapy for PDAC, overcoming chemoresistance.
Keywords: Cancer therapy; Drug-resistance; Ductal adenocarcinomas; Gemcitabine; Gene editing; Genes mutation; Nanoliposomes; P53 gene; Pancreatic cancers; Protein delivery; Carcinoma, Pancreatic Ductal; Cell Line, Tumor; Drug Resistance, Neoplasm; Gene Editing; Humans; Pancreatic Neoplasms; Pharmaceutical Preparations; Drug-resistance; Gene editing; Nanoliposome; Pancreatic cancer; Protein delivery